The association of depressive symptoms in patients with acute myocardial infarction in a regional hospital in Durban, South Africa - Sookan, Chiara; Ranjith, Naresh; Sartorius, Ben; Ramlall, Suvira (SA Heart Journal, 2018)
Objective: To examine the association of depressive symptoms and contributing psychosocial factors during hospitalisation and 1-month post discharge in patients with acute myocardial infarction (MI). Methods and results: The study population comprised consecutive patients from a multi-ethnic background, admitted June 2015 - November 2015 to the Coronary Care Unit at R. K. Khan Hospital, Durban, South Africa, with a diagnosis of MI. Demographic and clinical data stored in a specialised electronic cardiac database were extracted for all patients. Patients were screened for depressive symptoms using the Cardiac Depression Scale (CDS). Levels of perceived stress were evaluated using the 4-item Perceived Stress Scale (4-PSS). The study cohort consisted of 117 patients with a mean age of 58.16 ± 11.12 years, the majority of whom were males (70%, mean age 56.54 ± 1.23 years) and 30% females (mean age 61.97 ± 1.75 years). Forty-nine percent of the participants were diagnosed with depressive symptoms with a significantly greater number of females experiencing depressive symptoms compared to males (p <0.01). Patients with depressive symptoms were more likely to have a previous history of depression (p=0.02), positive family history of depression (p=0.04), greater non-adherence to their medication (p <0.01) and lower levels of physical activity (p <0.01). Depressed patients also reported higher levels of stress on voluntary (p <0.01) and subjective rating (p <0.01), experienced greater financial stress (p <0.01), major life events (p <0.01) and had higher 4–PSS scores (p <0.01). Thirteen percent of patients experienced major adverse cardiac events (MACE) with a significantly greater number of events found in those with depressive symptoms (p <0.01). Conclusion: Depressive symptoms are a common finding in a South African population presenting with MI. They are linked to higher rates of MACE, a previous history and/or family history of depression, greater stress levels and major life events. Females with MI are significantly more likely to present with depressive symptoms. These findings suggest that patients with MI should be screened for depressive symptoms and psychosocial factors as this may serve as an important arena for research and therapeutic intervention.